TIPOLOGI KESALAHAN IMLA’ VISUAL-MEKANIS: STRATEGI REDUKSI PROBLEMATIKA MENULIS ARAB SISWA MADRASAH TSANAWIYYAH USWATUN HASANAH - Abdul Rosyid; Dzikri Ahmad Fauzi; Fadhli Fakhrurrozi Furkony; Fitraman; Zulli Umri Siregar (PT. Hasba Edukasi Mandiri, 2026)
This study aims to identify and analyze the typology of imlā’ (orthography) errors in Arabic writing skills among students at MTs Uswatun Hasanah. A descriptive quantitative method was employed, utilizing error analysis techniques on 30 students. Data were collected through writing tests, yielding a corpus of 120 identified errors classified into ten orthographic categories. The findings reveal that the most dominant error is the inability to distinguish between visually similar letters (تشابه الحروف), accounting for 21.67% of total errors. Other significant findings include incorrect dot placement (18.33%) and violations of letter-connection rules (22.5%), while the omission of diacritical marks (harakat) recorded the lowest frequency (3.33%). This study concludes that students' writing problems are primarily visual and mechanical, indicating weak grapheme perception and motor coordination. These findings contribute to Arabic pedagogy by recommending strategic interventions such as directed writing activities and continuous written feedback to reduce orthographic errors at the secondary education level.